Nanocavity induced light concentration for energy efficient heat assisted magnetic recording media. (August 2018) - Deng, Chenhua; Song, Haomin; Parry, James; Liu, Yihao; He, Shuli; Xu, Xiaohong; Gan, Qiaoqiang; Zeng, Hao
Abstract: Enhancing light absorption in the recording media layer can improve the energy efficiency and prolong the device lifetime in heat assisted magnetic recording (HAMR). In this work, we report the design and implementation of a resonant nanocavity structure to enhance the light-matter interaction within an ultrathin FePt layer. In a Ag/SiO2 /FePt trilayer structure, the thickness of the dielectric SiO2 layer is systematically tuned to reach maximum light absorption at the wavelength of 830 nm. In the optimized structure, the light reflection is reduced by more than 50%. This results in effective laser heating of the FePt layer, as imaged by an infrared camera. The scheme is highly scalable for thinner FePt layers and shorter wavelengths to be used in future HAMR technologies. Graphical abstract: fx1 Highlights: A resonant nanocavity structure was designed and fabricated to concentrate light in the media layer for heat assisted magnetic recording. A 10 nm FePt layer in the nanocavity absorbs 87% of the incident light at the wavelength of 830 nm. The absorbed light is converted into heat to raise the temperature of the FePt layer, with greatly enhanced energy efficiency.